Deliverable 6.9 Support to Business Planning and Development - Buch, Erik; Fernández, Vicente; Aarnes, Øivin (Zenodo, 2022)
Climate warming in the Arctic Region opens up for new or changes and expansion of existing maritime business activities. The future business development perspectives for three important components of the Arctic Blue Economy –maritime transport via the Arctic Ocean, cruise industry in the Svalbard area and fishery in the Barents Sea has been analyzed. The maritime transport and cruise industry will potentially increase substantially over the coming years due to retreat of Arctic sea ice.In 2020 and 2021 the Covid-19 pandemic had severe negative impact on the cruise industry, whereas in 2022 the cruise traffic in the Arctic has recovered and was at the same level as the peak year in 2019. Barents Sea fishery is among the most important in Europe and represent a significant economic value for the industry. However, climate change with associated ecosystem changes will have impact on the stock composition and distribution, and consequently on the commercial fisheries. Entering into operations in the harsh Arctic environment requires good knowledge and understanding of the physical environmental conditions to ensure a sound decision process on economy, efficiency, safety of ship, crew and cargo and protection of the vulnerable Arctic environment. Therefore, examples of basic statistical analysis of relevant parameters like sea ice, wind, waves, temperature and salinity has been performed to outline the trends in change of environmental condition of importance for maritime operations in the Arctic. Additionally, operational meteorological and oceanographic near real time products and services are important when actually operating in the area. Satellite observations and outputs from numerical models are essential data sources for generation of operational products and services; but the trustworthiness of the information’s from these two data sources depends critically on the availability of in situ observations of key variables for assimilation in the models and especially for validation of quality of the generated ...